Hubungan Pengetahuan Tentang Anemia, Kepatuhan Konsumsi Tablet Fe, Dan Status Gizi Dengan Kejadian Anemia Pada Ibu Hamil Di Wilayah Kerja Puskesmas Batipuh II - Hidayah Afnas, Nur; Widya, Widya Francisca (Jurnal Medisains Kesehatan, 2024)
Pregnancy is a condition where a woman is carrying a fetus in her womb which is the result of sperm cells and ovum cells. Anemia often occurs, especially in pregnant women due to lack of iron (Fe) consumption. Data from the World Health Organization (WHO) in 2017, the prevalence of anemia is still high, namely globally the prevalence of anemia in pregnant women worldwide is 43.9%. The purpose of this study was to see how the relationship between knowledge about anemia, compliance with Fe Tablet Consumption, and Nutritional Status with the incidence of anemia in pregnant women. This study used a quantitative research method with a cross-sectional approach, sampling by purposive sampling. Data analysis using Univariate and Bivariate. The results of this study showed that 75% of pregnant women had good knowledge, 75% of pregnant women were compliant in consuming Fe tablets, 75% of pregnant women with normal nutritional status, and 75% of pregnant women did not experience anemia. The conclusion is that there is a relationship between knowledge about anemia, fulfillment of Fe Tablet consumption, and Nutritional Status with the incidence of anemia in pregnant women in the Batipuh II Health Center area.